3D printing‐based full‐scale human brain for diverse applications - Weijian Hua; Cheng Zhang; Lily Raymond; Kellen Mitchell; Lai Wen; Ying Yang; Danyang Zhao; Shu Liu; Yifei Jin (Brain-X, 2023)
Abstract Surgery is the most frequent treatment for patients with brain tumors. The construction of full‐scale human brain models, which is still challenging to realize via current manufacturing techniques, can effectively train surgeons before brain tumor surgeries. This paper aims to develop a set of three‐dimensional (3D) printing approaches to fabricate customized full‐scale human brain models for surgery training as well as specialized brain patches for wound healing after surgery. First, a brain patch designed to fit a wound's shape and size can be easily printed in and collected from a stimuli‐responsive yield‐stress support bath. Then, an inverse 3D printing strategy, called “peeling‐boiled‐eggs,” is proposed to fabricate full‐scale human brain models. In this strategy, the contour layer of a brain model is printed using a sacrificial ink to envelop the target brain core within a photocurable yield‐stress support bath. After crosslinking the contour layer, the as‐printed model can be harvested from the bath to photo crosslink the brain core, which can be eventually released by liquefying the contour layer. Both the brain patch and full‐scale human brain model are successfully printed to mimic the scenario of wound healing after removing a brain tumor, validating the effectiveness of the proposed 3D printing approaches.